Let's solve your equation step-by-step.<span><span><span><span> x2</span>+<span>5x</span></span>−6</span>=0</span><span />
<span> </span>Step 1: Factor left side of equation.<span><span><span> (<span>x−1</span>)</span><span>(<span>x+6</span>)</span></span>=0</span>
<span /><span> </span>Step 2: Set factors equal to 0.<span><span><span> x−1</span>=<span><span><span><span><span>0</span> or </span></span>x</span>+6</span></span>=0</span><span> </span><span> </span><span><span>x=<span><span><span><span>1</span> or </span></span>x</span></span>=<span>−<span>6</span></span></span>